KODE SIMBOLIK DAN KODE GNONIK MANTRA RITUAL MAPPANRE LEMBA NELAYAN SUMPANG PADA MASYARAKAT BUGIS PAREPARE - Saskia Anggi Dwi Maharani; Anshari Anshari; Andi Agussalim Aj (Universitas Negeri Makassar)
Symbolic Code and Gnonic Code of Mappanre Lemba Ritual Mantra for Sumpang Fishermen in the Bugis Parepare Community. This study aims to determine the symbolic and gnomic code of mantras. This research is a descriptive qualitative research. The research data is the mantra text and the translation of the mantra text. This research uses primary and secondary data sources. Data obtained through observation; and field research. The analysis technique is the analysis of the relationship between grammatical meanings, while combinatorial meaning analysis is used to interpret connotations and rhetoric. The results showed that the ritual mantra of Mappanre Lemba fisherman Sumpang contained symbolic codes of religion, nature, and objects. This mantra contains a gnonic code on offerings in ritual ceremonies.